Principle of a two-output-difference interferometer for removing the most important interference distortions. Issue 19 (11th November 2018) - Yang, Qinghua; Liu, Lixin; Lv, Pei
ABSTRACT: This paper presents a two-output-difference interferometer for removing the most important interference distortions caused by nonlinear detectors. These distortions can be removed not only because the resulting interferogram is composed of the difference between the signals of the two detectors, but also because the modulated signals at each output have the same amplitude and opposite phases. Due to the use of two corner-cube mirrors fixed as a single moving element, the tilt and shearing problem will disappear. The effect of the corner-cube mirror deviation angle and the plane mirror tilt angle are investigated in detail, and the formulas of their tolerance are derived by means of modulation depth and phase error. The advantage of the interferometer enables it to be suitable for Fourier transform spectrometers.